Educational Programs on Mental Health: Impact on Stigma Reduction in Schools - Cahyono, Intim; Palupi, Jenie; Maryanti, Syiska Atik (Research Psychologie, Orientation et Conseil, 2024)
Mental health stigma is a major barrier to seeking help in schools, often resulting in negative attitudes, misconceptions, and social exclusion, which can worsen mental health and academic outcomes. Educational programs aimed at raising awareness have been suggested as interventions to reduce stigma, but limited evidence exists on their effectiveness. This study evaluates the impact of educational programs on reducing mental health stigma in schools. A quasi-experimental design was used, involving 300 high school students. The experimental group (150 students) participated in a series of workshops and discussions focused on increasing knowledge and empathy toward mental health issues, while the control group (150 students) received no intervention. Data were collected using the Mental Health Knowledge Schedule (MAKS) and the Social Distance Scale (SDS) and analyzed through paired sample t-tests and ANCOVA. Results showed a 40% increase in knowledge scores and a 35% decrease in social distance scores in the experimental group, indicating improved attitudes and reduced discriminatory behaviors compared to the control group. Qualitative feedback revealed increased empathy and willingness to support peers with mental health challenges. The study concludes that structured mental health education programs effectively reduce stigma in schools, fostering a more supportive and inclusive environment.